2015
DOI: 10.1186/s12889-015-1376-3
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis risk factors among tuberculosis patients in Kampala, Uganda: implications for tuberculosis control

Abstract: BackgroundSlow decline in the incidence of tuberculosis (TB) has been observed in most high TB burden countries. Knowledge of the prevalence of different TB risk factors can help expand TB control strategies. However with the exception of Human Immunodeficiency Virus (HIV) the prevalence of the other TB risk factors are poorly studied in Uganda. We aimed to determine the prevalence of different TB risk factors and TB disease presentation among TB patients in Kampala Uganda.MethodsWe assessed 365 adult TB patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 34 publications
11
73
3
3
Order By: Relevance
“…According to Chongqing Statistical Yearbook, the annual income of farmers was less than half of urban residents. MDR/RR-TB were closely associated with poverty [22-24]. Medical services for MDR/RR-TB were often poorly accessible in rural areas [25].…”
Section: Discussionmentioning
confidence: 99%
“…According to Chongqing Statistical Yearbook, the annual income of farmers was less than half of urban residents. MDR/RR-TB were closely associated with poverty [22-24]. Medical services for MDR/RR-TB were often poorly accessible in rural areas [25].…”
Section: Discussionmentioning
confidence: 99%
“…We did not include national measures of more proximal risk factors such as alcohol use, malnutrition, or overcrowding despite the evidence of their association with TB. 13-15 .This was done because we believe these putative risk factors to be downstream on the causal pathway from social protection to tuberculosis.…”
Section: Methodsmentioning
confidence: 99%
“…96 Surveys have shown that the prevalence of smoking among confirmed and presumptive TB patients is higher than in the general population. 97, 98 Continued smoking during TB treatment is also associated with worse TB treatment outcomes (treatment failure and death). 99, 100 There is good evidence that smoking cessation works for TB patients: abstinence rates greater than 50% can be achieved at the end of TB treatment with simple interventions such as brief advice.…”
Section: Patients With Chronic Diseasesmentioning
confidence: 99%